PRONUNCIATION ERRORS MADE BY THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF UNIVERSITAS RIAU - Aziz, Abd; ', Jismulatif; ', M. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research entitled “Pronunciation Errors Made by the Fourth Semester Students of English Department of Universitas Riau”. The aims of this research is to find out the characteristics of errors commonly occur in English pronunciation errors and the causes of errors made by the fourth semester students of English Department at FKIP of Universitas Riau commonly. This is a descriptive qualitative that analyzed about pronunciation errors include vowels, consonants, diphthongs, which pronounced by the fourth semester students of English Department of FKIP Universitas Riau. In conducting this research, the group of population was selected to be a participant by using purposive sampling. There were 78 population and only 39 students as the participants. The test was taken in audio recording. After analyzing the data, from the three aspects that writer analyzed it was found some data and concluded that pronunciation error were made by the fourth semester students of English department of Universitas Riau in high error. There were was error in vowel 82.05 %, consonants with 41.02 % and diphthong 38.46 %.Keywords: Pronunciation, Errors, Analysis and Students.